2016
DOI: 10.1177/1352458516631038
|View full text |Cite
|
Sign up to set email alerts
|

Children with multiphasic disseminated encephalomyelitis and antibodies to the myelin oligodendrocyte glycoprotein (MOG): Extending the spectrum of MOG antibody positive diseases

Abstract: Children with MDEM and persisting MOG antibodies constitute a distinct entity of relapsing demyelinating events and extend the spectrum of MOG antibody-associated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
126
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 26 publications
13
126
1
2
Order By: Relevance
“…Anti-MOG antibody titers of monophasic ADEM patients declined or became negative over the course of months to years [6]. However, patients with persistently high anti-MOG antibody titers experienced a recurrent disease course [6, 7]. The anti-MOG antibody titer of the present case became negative and did not show recurrence.…”
Section: Discussionmentioning
confidence: 79%
“…Anti-MOG antibody titers of monophasic ADEM patients declined or became negative over the course of months to years [6]. However, patients with persistently high anti-MOG antibody titers experienced a recurrent disease course [6, 7]. The anti-MOG antibody titer of the present case became negative and did not show recurrence.…”
Section: Discussionmentioning
confidence: 79%
“…Relapsing cases were assigned the following diagnostic categories: (1) multiple sclerosis, fulfilling the 2013 International Pediatric Multiple Sclerosis Study Group consensus criteria and the 2010 revised McDonald criteria; (2) NMOSD, fulfilling the 2015 Wingerchuk criteria; (3) multiphasic disseminated encephalomyelitis and ADEM‐optic neuritis fulfilling the 2013 International Pediatric Multiple Sclerosis Study Group consensus criteria; and (4) recurrent demyelination in a single central nervous system (CNS) area without evidence of clinically silent disease (for example relapsing optic neuritis).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, MOG‐Ab have been reported in about 40% of children at first presentation of an acquired demyelinating syndrome, with two studies from the UK/France and the Netherlands suggesting that MOG‐Ab identified at onset are associated with a non‐multiple sclerosis disease course. Although initially reported in predominantly monophasic disease, MOG‐Ab have been detected in patients with multiphasic disseminated encephalomyelitis, recurrent optic neuritis, and acute disseminated encephalomyelitis (ADEM) followed by recurrent or monophasic optic neuritis, and in both adults and children with NMOSD without AQP4‐Ab. Two recent reports identified MOG‐Ab and AQP4‐Ab in 28 out of 35 and 34 out of 48 children with non‐multiple sclerosis relapsing demyelination.…”
mentioning
confidence: 99%
“…106 In pediatric cohorts, MOG-Ab was frequently found in patients with ADEM (up to 43%), most of whom had two or more episode of attacks (up to 100%). 117 …”
Section: Differential Diagnosis Of Nmosdmentioning
confidence: 99%